Immortal nights - Sands, Lynsay (Sands, Lynsay. Argeneau series., 2017)
When she rescues a naked man from a plane's cargo hold, Abigail Forsythe, miles away from civilization and hunted by his kidnappers, finds a passion like no other in the arms of this immortal creature.